A207 UNDISCLOSED PAYMENTS BY PHARMACEUTICAL AND MEDICAL DEVICE MANUFACTURERS TO AUTHORS OF ENDOSCOPY GUIDELINES IN THE UNITED STATES. (15th March 2019) - Rumman, A; Bansal, R; Scaffidi, M A; Bukhari, A; Khan, R; Dhillon, J; Genis, S; Grover, S C
Abstract: Background: Payments from pharmaceutical and medical device manufacturers to authors of clinical practice guidelines (CPG) may influence practice recommendations. It is therefore important to evaluate the completeness of financial conflict of interest (FCOI) declarations among CPG authors. Aims: We aimed to assess the prevalence, nature and magnitude of undisclosed industry payments to authors of endoscopy guidelines. Methods: We performed a cross-sectional analysis of undisclosed industry payments to authors of gastrointestinal endoscopy guidelines published by the American College of Gastroenterology (ACG) and the American Society of Gastrointestinal Endoscopy (ASGE) between 2014 and 2017. For each CPG author, we identified industry payments through the payment declaration section of CPGs and the Centre for Medicare and Medicaid Services Open Payments (CMS-OP) database. We calculated the prevalence of CPG authors with declared and undeclared payments, as well as the monetary value and type of undeclared payments. For each CPG, payments were assessed for the calendar year of publication and the calendar year prior. Results: Thirty-eight CPGs were included in the analysis comprising 581 author entries (90 unique individuals; 66.8% male, 92.8% physicians, 65.4% affiliated with an academic hospital). Payments were disclosed in the CPG document by 126 authors (21.7%). A CMS-OP record was identified for 460 authors (79.2%), and of those – 406 (88.3%) had undeclared payments over a two-year period. Of those, 97 (23.9%) authors received undisclosed payments relating directly to a product or service addressed in the CPG. Undisclosed payments were reported as general payments (mean US$33, 142) or research funding (mean US$22, 883). Undisclosed payments were received from a mean of 4 payers (range 1–19). Conclusions: There is a high burden of undisclosed payments by pharmaceutical and medical device manufacturers to authors of endoscopy guidelines in the United States. Given the potential impact of these undisclosed payments on CPGs, stricter policies on conflict of interest disclosures are needed. Funding Agencies: None